Safety and durable patency of tunneled hemodialysis catheter inserted without fluoroscopy - Kim, Do Hyoung; Youn, Sojung; Ban, Tae Hyun; Choi, Bum Soon; Kim, Byung Soo; Park, Cheol Whee; Yang, Chul Woo; Park, Hoon Suk (Kidney research and clinical practice, 2023)
A tunneled hemodialysis (HD) catheter is preferred due to its lower incidence of infection and malfunction than non-tunneled ones. For safer insertion, fluoroscopic guidance is desirable. However, if the patient is unstable, transfer to the fluoroscopy may be impossible or inappropriate. From June 2019 to September 2022, 81 tunneled HD catheter insertion cases performed under ultrasound guidance without fluoroscopy and 474 cases with fluoroscopy in our institutional HD catheter cohort were retrospectively compared. Immediate complications, later catheter-associated problems, including infections and catheter dysfunction, were comparable between the two groups (p = 0.20 and p = 0.37, respectively). The patency of tunneled catheters inserted without fluoroscopy was comparable to the patency of tunneled catheters inserted with fluoroscopic guidance (p = 0.90). Tunneled HD catheter insertion without fluoroscopy can be performed safely and has durable patency compared to the insertion with fluoroscopy. Therefore, this method can be considered for the selected unstable patients (e.g., ventilator care) in the intensive care unit.